Space-Time Turbo Coded Modulation: Design and Applications - Tujkovic Djordje; Juntti Markku; Latva-aho Matti (EURASIP Journal on Advances in Signal Processing, 2002)
A design method for recursive space-time trellis codes and parallel-concatenated space-time turbo coded modulation is proposed that can be applied to an arbitrary existing space-time trellis code. The method enables a large, systematic increase in coding gain while preserving the maximum transmit diversity gain and bandwidth efficiency property of the considered space-time trellis code. Applying the above method to Tarokh et al. space-time trellis codes, significant performance improvements can be obtained even with extremely short input information frames. The application of space-time turbo coded modulation to the space-frequency domain is also proposed in this paper. Exploiting the bandwidth efficient orthogonal frequency division modulation (OFDM), multiple transmit antennas and large frequency selectivity offered by typical low mobility indoor environments, the proposed space-frequency turbo coded modulation performs within 2.5dB of the outage capacity for a variety of practical wideband multiple-input multiple-output (MIMO) radio channels.